2017
DOI: 10.1080/21691401.2017.1307208
|View full text |Cite
|
Sign up to set email alerts
|

An overview application of silver nanoparticles in inhibition of herpes simplex virus

Abstract: Nanoscale particles and molecules are a potential different for the treatment of disease because they have distinctive biologic property based on their structure and size, which is different from traditional small-molecule drugs. The antimicrobial mechanisms of silver nanoparticles include the formation of free radicals damaging the bacterial membranes, interactions with DNA, adhesion to cell surface altering the membrane properties, and enzyme damage. In this review, we focus on applications of silver nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 49 publications
0
37
0
1
Order By: Relevance
“…[64,65] These antiviral mechanisms are mainly caused by stress in infected cells (due to physical contact), generation of reactive oxygen species (ROS), interactions with DNA and enzymatic damage. [66] The first mechanism is through the binding of Ag NPs with sulfur residues from the virus's surface glycoproteins, preventing interaction with the receptor and its entry into the host cell. [67,68] The second mechanism involves the passage of Ag NPs through the cell membrane that consequently, it ends up effectively blocking the transcription factors necessary for the adequate assembly of the viral progeny.…”
Section: Resultsmentioning
confidence: 99%
“…[64,65] These antiviral mechanisms are mainly caused by stress in infected cells (due to physical contact), generation of reactive oxygen species (ROS), interactions with DNA and enzymatic damage. [66] The first mechanism is through the binding of Ag NPs with sulfur residues from the virus's surface glycoproteins, preventing interaction with the receptor and its entry into the host cell. [67,68] The second mechanism involves the passage of Ag NPs through the cell membrane that consequently, it ends up effectively blocking the transcription factors necessary for the adequate assembly of the viral progeny.…”
Section: Resultsmentioning
confidence: 99%
“…MiRNAs are generally involved in post-transcriptional gene regulation. They are highly conserved among a wide range of species [26]. MiRNAs are key regulators of cellular pathways, and they appear to play an important role in tumourigenesis [27].…”
Section: Mirna and Cancermentioning
confidence: 99%
“…For instance, AgNPs have been reported as biomedical therapeutic agents, such as wound dressings and long-term burn care products [57], and anti-bacterial lotions containing silver nanoparticles are now commercially available. However, silver nanoparticle-based antiviral agents are still in the infancy stage, and very few reports have been published about their viricidal activity [58,59]. The latest reports have shown that silver nanoparticles exhibit antiviral activities against influenza A virus, hepatitis B virus, human parainfluenza virus, herpes simplex virus, and human immunodeficiency virus [60].…”
Section: Silver Nanoparticlesmentioning
confidence: 99%